Morphometry and Histology of the Testicular Capsule and Peritubular Tissue of Testis of Guinea fowl (Numida meleagris) - P, Dharani; UshaKumary, S.; Venkatesan, S.; Joseph, Cecilia; Ramesh, Geetha (Indian Journal of Veterinary Anatomy, 2018)
The aim of the present study was to document the detailed histology of capsule and peritubular tissue of the guinea fowl testis to understand its role in support and transport of spermatozoa. The work was conducted in 30 birds of five age groups viz., 5, 8, 12, 15 and 18 months. The thickness of the capsule was not increased with the age. The capsule was made up of three layers of tissue viz., outer tunica serosa, very thick tunica albuginea and poorly differentiated inner tunica vasculosa. The bulk of the tunica albuginea was composed of smoothmuscle fibres and compact collagen fibres. The peritubular tissue was a thin layer of connective tissue made up of collagen and reticular fibres around the basement membrane of the seminiferous tubule. The myoid (smooth muscle cells) and fibroblast cells were the common cell population in the peritubular tissue. The presence of smooth muscle cells in the capsule and peritubular tissue could be attributed to the transport of spermatozoa whereas the collagen fibres and fibroblasts for the mechanical support.